Disrupting Age Stereotypes in Theatre for Young Audiences with Older-Bodied Puppets - Henderson, Julia (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
Although expressions of aging and old age differ across other identity categories, they most often yoke aging to notions of deterioration and loss. Young audiences are exposed to this narrative of decline through wide-ranging cultural references in advertising, cartoons, fairy tales, children’s books, and theatre. However, various forms of theatre can also reimagine age narratives in positive ways. In this article, Henderson uses close performance analysis, analysis of archival video, and an interview with Vancouver theatre artist Chris McGregor to examine the Vancouver-based TYA puppet plays The Little Old Man by Theatre Bagger Arts Society and Somebody Loves You, Mr. Hatch by Axis Theatre. Both plays share a number of age-related themes and establish nuanced, positive messages about aging, older age, and intergenerational relations. By drawing on Steve Tillis’s theory of puppetry and Anne Davis Basting’s depth model of aging, Henderson argues that puppets can be used to interrupt negative age stereotypes and hostile age-related narrative tropes, and encourage children to reimagine old age, aging, and relationships with older people in complex and hopeful ways. In the case of these two plays, Henderson contends that they interrupt age stereotypes by portraying children and older characters as having agency, foregrounding positive intergenerational relations, and reimagining decline. They do this, Henderson argues, through their themes, aesthetics and performance styles, and the embodied performances of the handlers in conjunction with their animation of the puppets.